Kilani, Abdullah Ibrahim. “The Islamic Worldview and its Impact in Determining Foreign Policy,” Year 12, Issue 45 (Summer 1427 AH/ 2006 CE), Pp. 25-64. - الكيلاني عبد الله إبراهيم (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2006)
Abdullah Kilani’s article begins with incidents from the life of Prophet Muhammad (ṢAAS) and the Companions, and emphasizes that attention to world public opinion and keenness to preserve the integrity of the image of Muslims when applying particular rulings is what is dictated by the correct application of the sacred text. His article discusses the holistic vision in the guidance of the Prophet and his Companions, and the holistic guiding principles of ijtihad with respect to global affairs, including how to understand the notions of dār al-Islām (the abode of Islam) and dār al-ḥarb (the abode of war) in light of a holistic view of the globe. It also addresses the positions of the different schools of thought as well as contemporary scholars on territorial divisions of the world.